GENETIC ASSESSMENT STUDIES FOR YIELD AND YIELD PARAMETERS IN DIVERSE GENOTYPES OF EGGPLANT ( ARAMETERS IN DIVERSE GENOTYPES OF EGGPLANT (Solanum melongena melongena L.) - ASHUTOSH KUMAR,; SINGH, ANAND KUMAR; MOHARANA, DURGA PRASAD; SINGH , VAIBHAV; PUSHPENDRA SINGH, (The Bioscan, 2017)
In the present investigation an attempt was made to assess the phenotypic and genotypic coefficient of variation, heritability, genetic advance, and genetic gain for various quantitative traits in eggplant during Kharif season of 2015 at Vegetable Research Farm of Department of Horticulture, Institute of Agricultural Sciences, Banaras Hindu University , Varanasi. From the Analysis of variance it was clear that there were significant differences among all the 17 genotypes of eggplant. Highest values of GCV (31.26) and PCV (31.65) were obtained for average fruit weight whereas maximum heritability (98.33%) was found in fruit length. High values for both genetic advance (79.45%) as well as genetic gain (63.59%) were exhibited in fruit weight. It was noted that all the research works conducted for studying the diverse genotypes of eggplant is fulfilled as indicated by wide range of variation among genotypes and also relative parameters obtained in fourteen characters.